Studying Transport Models with the Shortest Time According to the Neutrosophic Logic - Maissam Jdid (Neutrosophic Sets and Systems, 2023)
Time factor plays an important role in many issues, and the most important of these issues is the issue of transportation, when we need to transport perishable materials such as milk, medicines ,blood,….. etc. or develop war plans to secure the requirements of battle of ammunition - food - and soldiers …..etc., at maximum speed, we need a careful scientific study that enables us to avoid losses, so the researchers studied transport models in the shortest possible time using the values of classic logic and the best solution for such models is a specific value subject to increase or decrease because there is nothing certain in the real reality, all the results of the studies are related to the surrounding conditions of the system under study, due to the sensitivity of these issues had to be reformulated according to a science that takes into account all the cases that the system can go through so that we can take all possible precautions that help us reduce losses and secure the required in the shortest possible time, we have in This research formulates transport models with the shortest time and we presented a special way to solve such models using neutrosophic values, based on the concept of the neutrosophic linear mathematical model, a model that has something of non-determination (indeterminacy) and we reached transport models with the shortest time that are considered a generalization of the existing models because they give us optimal neutrosophic values for time.